Aspects of the Reproductive Biology and Growth of the Mississippi Silvery Minnow, Hybognathus nuchalis (Agassiz, 1855) (Teleostei: Cyprinidae) from the Pearl River, Louisiana. - Arely Ramírez-García; Kyle R Piller (Southeastern Fishes Council Proceedings, 2018)
The reproductive biology and growth of the Mississippi Silvery Minnow, Hybognathus nuchalis, is described from multiple sites in the Pearl River, Louisiana. Individuals were collected from August 2011 to August 2012. Ovarian weights, expressed as a percentage of body weights, peaked in December. Size structure ranged from 29.0 to 60.0 mm SL for females and 25.0 to 56.0 mm SL for males. Mature ova were found from November to January. Females reached first maturity (L50) at 37.0 mm SL and L50 for males is at 41.0 mm SL. Sex ratio (females:males) is biased towards females (X2= 18.57 p < 0.05). Fecundity of mature individuals ranged from 118 to 830 ova (mean 433±256.8 SD) in fish 30-50 mm SL. There was negative allometric growth for both sexes and there was a significant relationship significant between SL and body weight for both sex (R2=0.9, p<0.05).
Keywords: Cyprinidae; life-history; reproduction